Hubungan Penerapan Prinsip-prinsip Andragogi dengan Hasil Belajar Peserta Pelatihan Menjahit Pakaian - Sri Mulyana (Universitas Negeri Padang, 2020)
This study aims to reveal an overview of the application of andragogical principles in training, the learning outcomes of the training participants to sew clothes, and reveal the relationship between the application of andragogical principles and the learning outcomes of the training participants to sew clothes based on the initial observations that the author has made, located at Balai Work Training (BLK) in Padang. The results of the observations show that the high learning outcomes of the training participants are thought to be caused by the application of andragogical principles to the sewing training. This type of research is a correlational study that uses a quantitative approach. The population in this study was the training participants in sewing clothes for the January-March period this year. The sampling technique is saturated sampling and the sample is the whole population. The data collection technique used was a questionnaire and the tools used were questionnaires. The data analysis technique used the percentage formula and the Spearman Rho formula. The results of this study indicate that: 1) the application of andragogical principles in sewing good clothes; 2) the learning outcomes of the training participants to sew clothes are classified as good; 3) there is a significant relationship between the application of andragogical principles and learning outcomes in sewing training at the Vocational Training Center (BLK) in Padang. The suggestion of this research is that it is hoped that the instructor can deepen knowledge in teaching adults so that the results obtained are more optimal. Although in practice it has been implemented well. Keywords: Andragogy Principles, Learning Outcomes